First trimester uterine rupture-a rare but catastrophic event: a case report - Tripathi, Suchita; Srivastava, Sugandh; Gupta, Shruti; Gupta, Renu; Gupta , Neena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Uterine rupture is a rare but life threatening obstetrical emergency. It often occurs at term during trail of labour but rarely may occur during early pregnancy in first trimester. Here, we report a case of 28 years, G2P1+0L0 at 3 months of pregnancy with fundal rupture in shock with history of previous caesarean section. Ultrasound report revealed massive hemoperitoneum (2 litres) with dead fetus lying outside the uterine cavity. Emergency laparotomy was performed and uterine repair was done. The differential diagnosis for hemoperitoneum is early pregnancy includes bleeding corpus luteum, heterotropic pregnancy or ectopic pregnancy and molar pregnancy with secondary invasion. The possibility of uterine rupture should also be kept in mind. Prompt diagnosis and early management is important to reduce the morbidity and mortality.